KONSEP PERENCANAAN PENDIDIKAN INKLUSIF DI SEKOLAH DASAR - Yawati, Yunita Suliti; Bakri, Nofri; Elya, Zurtina; Asmendri, Asmendri; Sari, Milya (Diklat Review : Jurnal manajemen pendidikan dan pelatihan, 2023)
Abstract: Educational planning is the starting point or point of view used in the process of implementing education with systematic activity steps to achieve educational goals effectively and efficiently. Educational planning plays a role in providing clarity of direction in the education delivery process. Therefore, an educational planner is required to have the ability to prepare a design using one type of educational planning approach. The educational planning approach for each type and level of education will be different, especially for inclusive education. Education is not only for normal children, but children who have special needs must get the same educational opportunities and opportunities as other normal children. In the Islamic view, education is an obligation both to understand Islamic obligations and to build culture/civilization. Inclusive education is a way or innovation to address educational equality for all Indonesian citizens, both normal children and those with special needs. Planning inclusive education related to Children with Special Needs (ABK) is a complex task and an important thing that must be done before implementing learning. Inclusive education is a conscious effort to mature humans through structured and sustainable efforts with an open, dynamic and rational learning system. To achieve peace and prosperity in the educational process, especially at the elementary school level, there is a need for educational planning where this will influence the process of achieving educational goals. Keywords: Inclusive Education, Educational Planning